Efficient computation of the flow around single fluid particles using an artificial boundary condition. (17th February 2014) - Weirich, D.; Köhne, M.; Bothe, D.
SUMMARY Two‐phase flows around fluid particles are often considered to be in infinite domains, to avoid influence of the domain walls. Numerical simulations, however, must be modeled with a bounded domain, thus introducing artificial boundaries. Modeling of fluid flow in a domain with such artificial boundaries requires a careful choice of suitable boundary conditions. Slip boundary conditions for example can have a large impact on the computational results if the domain is chosen to be too small, because they model impermeable walls. This paper introduces an artificial boundary condition for simulations of the flow around single rising or settling fluid particles based on the approximated decay behavior of the velocity and the pressure field in the surrounding liquid. This is applied to the simulation of rising gas bubbles in systems with a Reynolds number of up to 50, and the outcome is compared with experimental results and simulations with slip boundary condition. It is found that domain size can be reduced by a factor of about two compared with slip boundary conditions without loss of accuracy. Copyright © 2014 John Wiley & Sons, Ltd.